Insights from one American Indian tribe about heart health - Sarah de Loizaga; McCall Miller; Barbie Giambra; LeCario Benashley; Billie Bones; Samantha Buonfiglio; Gwendena Lee Gatewood; Amanda Paxson; Teresa Pestian; Rachel Sarnacki; Rhiannon Walker; Dawnafe Whitesinger; et al. (American Heart Journal Plus)
Background: American Indians are impacted by significant health disparities compared to the general US population, with cardiovascular disease as a leading cause of death. Additionally, many American Indian populations face significant barriers to accessing specialty cardiac care. For one American Indian Tribe in Eastern Arizona, barriers to care include long distances to travel for echocardiography or cardiology consultation and delays in diagnosis. The purpose of this study was to gain insight into tribal perspectives of heart health and priorities in the design of a hearthealth program. Methods: We used qualitative semi-structured interviews to examine Tribal experiences and perspectives surrounding heart health and health in general on Tribal lands. The Community Research Leadership Board assisted with developing the interview guide, recruitment, and data collection. Results: A total of 19 interviews were completed. We used thematic analysis and identified five primary themes: 1) Awareness leads to understanding and acceptance; 2) Systemic barriers impede heart-health care; 3) Community engagement supports a sustainable heart-health program; 4) Heart-health initiatives can be influenced by personal perspectives; and 5) Expanded resources enable engagement. Conclusion: Improvement in heart-health care and management is urgently needed for American Indian peoples who are disproportionately impacted by poor heart outcomes. Our findings suggest that a heart-health initiative for this Tribe needs to raise community awareness, address individual and systemic barriers, and leverage community strengths. These findings will directly inform planned persona development and community-based design workshops as we work toward a co-developed, impactful, and sustainable heart-health program.